Preparation of Aluminium Pillared Clay from Indonesian Montmorillonite and Its Catalytic Activity in Bio-Oil Cracking - Fatimah, Is; Hidayat, Arif; Himmi Setiawan, Khoirul (Asian Journal of Chemistry, 2010)
The preparation of aluminium pillared montmorillonite (Al-PILM) from Indonesian natural montmorillonite and its catalytic activity study in the bio-oil cracking has been investigated. The synthesis of Al-PILM catalyst was conducted through intercalation process of Al13 Keggin ion at the Al ratio of 5 mmol Al/g montmorillonite followed by dehydroxylation processing to get aluminium oxide pillar in montmorillonite interlayer. Catalyst characterization performed by XRD, surface area analyzer and surface acidity measurement and SEM. Activity test of material as catalyst in bio-oil cracking focused on the effect of Al-PILM utilization to the product distribution and liquid product composi-tion. The result showed that Al-PILM has higher activity to produce lighter fraction of hydrocarbon than montmorillonite. The increase in liquid product and selectivity to produce smaller hydrocarbon compounds attributed to the improvement of catalyst performance after pillarization.